Utilization of Audio Visual as a Learning Resource for History Subjects at SMA Mulia Pratama Case Study in Class X - Hardiyansyah*, Muhammad Ricky; Sumantri, Pulung; Nugraha, Muhammad Adika; Fitri, Hadiani (Universitas Syiah Kuala, 2023)
Progresses in science and innovation, particularly data innovation, significantly impact the readiness and execution of learning procedures. Media is a middle person like television, radio, slides, and written words, however it additionally incorporates individuals as learning assets or as exercises including conversations, workshops, field outings, reenactments, etc, which are molded to add understanding and change understudies' mentalities to increment information. This review utilized a subjective elucidating research technique, with the exploration area at Mulia Pratama Secondary School. The fundamental subjects in this review were history educators and understudies at Mulia Pratama Secondary School who zeroed in on learning exercises about Indonesian history material by using audiovisuals in history learning. In view of the consequences of exploration and conversation of the utilization of general media in learning Indonesian history for class X, SMA Mulia Pratama Learning stands out for additional understudies with the goal that it can cultivate learning inspiration. Learning materials become more clear in significance, making it simpler for understudies to figure out learning. Furthermore, understudies do additional learning exercises since they don't simply pay attention to the educator's clarification; they do different exercises, for example, noticing, doing, and illustrating.